Հարկային հարաբերությունների համակարգը և հարկային քաղաքականության արդյունավետության բարձրացման ուղիները Հայաստանի Հանրապետությունում - Վարդան Բաբկենի Բոստանջյան; Տիգրան Վլադիմիրի Հարությունյան (ՀՀ ԳԱԱ հրատ.)
Статья посвяшена проблемам формирования системы налоговых отношений, ее исследованию и оценке количественной зависимости между этими отношениями. Исследование последней проведено с помощью современных методов количественного анализа и эконометрических моделей, позволяющих обеспечить высокий уровень регулирования налогово-бюджетных отношений, повышения эффективности налоговой политики и разработки механизмов совершенствования налогового администрирования. The article discusses the issues of developing the system of tax relations, their study, and quantitative estimation of dependencies among these relations. The study of the latter ones has been carried out by applying the contemporary techniques of quantitative analysis and running regression equations that allows ensuring a higher level of accuracy while designing respective mechanisms to regulate fiscal relations, ensure higher effectiveness of the tax policy, and better tax administration processes.
Keywords: Հասարակական գիտություններ; Տնտեսագիտություն; Ֆինանսներ